(untitled) (Research, Society and Development, 2024)
Trigeminal Neuralgia (TN) is a chronic neurological condition characterized by recurrent and unilateral episodes of facial pain, with a stabbing, burning or electric shock sensation. The disease interferes with daily activities, resulting in poor quality of life for patients. This study presents a narrative review of the literature, which aims to investigate the efficacy and safety of carbamazepine compared to vixotrigine and erenumab in the treatment of trigeminal neuralgia, based on articles published in the last five years in the main scientific databases, including PubMed, Scielo and Google Scholar. After searching and excluding irrelevant articles, 22 relevant articles were used for the development of the research. TN is one of the most painful and debilitating neurological conditions, with carbamazepine being the first-line treatment, but with long-term side effects. Vixotrigine, a novel sodium channel blocker, has been shown to be effective and well tolerated in clinical trials, while erenumab, an antibody originally developed for migraine, has shown therapeutic potential in patients with refractory TN. This study highlights the need for further clinical research and larger patient populations to assess the efficacy of these new treatments and their integration into clinical practice, expanding the options for the safe and effective management of TN.